THE PERSONALITY OF ‘IBADURRAHMAN IN QUR’AN (Character Education Construction in Building Civilization) - Yundri Akhyar; Wilaela Wilaela (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Education should lead to creating human beings who believe in the Divine. Here, their personality in the characteristics of ‘Ibadurrahman is to become true believers, as mentioned in the Holy Qur’an. Such characteristics as the faithful servants of God are necessarily taught in Islamic education. The word ‘Ibadurrahman as stated in the Qur’an (Surah al-Furqan, verse 63-77) is indeed the core of character education. This article describes what and how the character of ‘Ibadurrahman works and how it constructs the objectives of Islamic education. Methodically, this article is a library research considering the data examined and analyzed are based on library references. The result shows the Holy Qur’an has set an example of human personality, a true believer who owns the character of ‘Ibadurrahman, the loving servant of God. To this end, the millennial character education must refer to constructing the personality of ‘Ibadurrahman to build civilization